Migração de metais por interação das embalagens com soluções parenterais - Bertagnolli, Denise de Castro (2008)
The administration of medication and nutrients via parenteral is very used nowadays. One of the risks of this procedure is the presence of contaminants, which depending on their nature may cause severe damage to the patients due to the direct way of the administration (in the circulatory stream). In this work we investigated the possibility of the containers to be sources of metals for solutions of parenteral nutrition. The investigated containers are made of different kinds of glass and plastic polymers, namely polypropylene, PVC and EVA. The system container/solution (amino acids, salts, glucose and lipids) individually stored, was submitted to the sterilization process and after that stored for a time period of approximately 10 months, since the shelf-life period of these formulations are generally 2 years. After the sterilization and at regular time intervals, aliquots of each solution were collected and their contents on Al, Pb, Cd, Fe, Cr, Mn, Ba, and Zn were measured by graphite furnace atomic absorption spectrometry. The containers were also analyzed for the determination of the amount of each metal they contained. These metals are either constituents of the container material, as Al in glasses, or impurities in the case of plastic polymers. All containers presented the metals investigated. The solutions, depending on their composition (species dissolved) were able to extract the metals either from the glass or the polymers. The highest extraction rates occurred in solutions of the amino acids cysteine and glutamic acid, and in solutions of NaHCO3. The metals released in higher concentration were Ba, Pb and Zn form plastic containers and Al, Pb and Zn form glass containers. A different behavior was observed among the plastic polymers, and the different kinds of glass. While EVA was the most inert polymer, the clear glass ampoule released the highest amount of metals into the solutions. Fifty commercial samples were analyzed as well, and the investigated metals were found in all of them. The commercial formulations presented the same tendency of the individual sample used in the study, either in relation to the behavior of the substance in solution or the container material.